Ethics management in libraries and other information services - Pulido, Margarita Pérez (Chandos Information Professional Series, 2018)
Ethics Management in Libraries and Other Information Services presents professional ethics from a managerial point-of-view, explaining how to implement ethical management systems in libraries and information services and presenting the necessary tools needed to understand the practical application of a system of ethical management based on ISO 26000: 2010. The examples and selected case studies will be helpful to professionals, teachers and students who want to both explore and apply ethics now and in the future.--Provided by publisher.